Reflexiones Acerca del Papel de la Mujer en la Reproducción Artificial Post Mortem (Analysis of the Role of Women in the Posthumous Reproduction) - Alma María Rodríguez Guitián (Oñati Socio-Legal Series)
This contribution focuses on the analysis of the role of women in the posthumous reproduction. In the first place, it studies whether the woman's right to have children should be subject to limits and, if so, to which ones. Second, it explores if the posthumous reproduction extends to lesbian couples, married or not, and finally it focuses on the relevance of the mother's will to decide the deceased to be registered as the parent of the child.